Pengaruh Temperatur reaksi terhadap Aktivitas Katalis Besi Molibdenum Oksida Berpromotor Kromium Oksida - Fikri Hasfita; Husni Husin (Industrial Engineering Journal, 2013)
Preparation of iron molybdenum oxide promoted chromium oxide (Cr2O3/Fe2 (MoO4) 3) hasbeen done. The sample is synthesized by precipitation method. The performance of the catalyst isevaluated by the catalytic oxidation of methanol to formaldehyde. For comparison, in this experimentalso use Fe2(MoO4)3 without promoter and Fe2 (MoO4)3 commercial. The samples are characterized by xray diffractometer (XRD) to determine its composition. XRD results indicate that the catalyst componentcomprised of Fe2 (MoO4)3, Fe2O3, and MoO3. The reaction is conducted in a tubular reactor with fixed-bedcatalyst, operating at temperatures of 250, 300, 350 °C, and atmospheric pressure. The products areanalyzed by Shimadzu gas chromatography using a porapak-Q column. The highest yield offormaldehyde of each catalyst, i.e: Fe2(MoO4)3, Cr2O3/Fe2 (MoO4)3 of 83%, 86% at temperatures of 300 °Cand Fe2(MoO4)3 commercial reach 96% at a temperature of 350 oC, respectively. The addition of Cr2O3 asa promoter shows increased the activity of iron molybdenum oxide catalysts.